2016
DOI: 10.20463/jenb.2016.06.20.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and dietary change ameliorate high fat diet induced obesity and insulin resistance via mTOR signaling pathway

Abstract: [Purpose]The purpose of this study was to investigate the effect of exercise and dietary change on obesity and insulin resistance and mTOR signaling protein levels in skeletal muscles of obese rats.[Methods]Sixty male Sprague-Dawley rats were divided into CO (Normal diet) and HF (High Fat diet) groups in order to induce obesity for 15 weeks. The rats were then subdivided into CO, COT (CO + Training), HF, HFT (HF + Training), HFND (Dietary change), and HFNDT (HFND + Training) groups (10 rats / group). The train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Regular exercise and caloric restriction are effective treatments for the regulation of body weight [17, 18]. In this study, as expected, HFD increased fat mass and body weight, but regular exercise without a caloric restriction inhibited the increase in weight gain.…”
Section: Discussionsupporting
confidence: 79%
“…Regular exercise and caloric restriction are effective treatments for the regulation of body weight [17, 18]. In this study, as expected, HFD increased fat mass and body weight, but regular exercise without a caloric restriction inhibited the increase in weight gain.…”
Section: Discussionsupporting
confidence: 79%
“…The mTOR/S6K1 pathway regulates the serine phosphorylation of IRS-1, and previous studies have showed that the increased phosphorylation of mTOR and S6K1 caused subcellular redistribution of IRS-1 and inactivation of IRS-1 by increasing its serine phosphorylation, leading to insulin resistance [27, 29, 30]. It has been reported by Bae et al [31] that exercise and dietary change stimulate the mTOR signaling pathway and ameliorate insulin resistance. Here, we found an increased phosphorylation of the mTOR/S6K1 pathway in the muscle cells after colorectal resection, while POC suppressed the activation of the mTOR/S6K1 pathway, and PIR was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…3). Strong evidence from preclinical studies has emerged to demonstrate that caloric restriction reduces obesity-related hyperactivation of mTOR complex 1 (mTORC1) in multiple tissues, including colon, pancreas and liver, in obese mice 55 , with diet and/or exercise interventions in mice and rats supporting these findings 137,138 . Exercise interventions in mice also demonstrated decreased kinase activity of mTOR in tumours of the liver 139 , suggesting that energy balance interventions have the potential to decrease tumour cell proliferation via the mTOR signalling pathway.…”
Section: Biological Mechanismsmentioning
confidence: 99%